2019
DOI: 10.3748/wjg.v25.i27.3649
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy with dendritic cells and cytokine-induced killer cells for hepatocellular carcinoma: A meta-analysis

Abstract: BACKGROUND Hepatocellular carcinoma (HCC) has been revealed as the second most common cause of cancer-related deaths worldwide. The introduction of cell-based immunotherapy, including dendritic cells (DCs) and cytokine-induced killer cells (CIKs), has brought HCC patients an effective benefit. However, the efficacy and necessity of cellular immunotherapy after different interventional therapy remains to be further explored. AIM To investigate the efficacy of cellular im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 53 publications
2
31
0
Order By: Relevance
“…Through three meta-analysis studies of more than 8 thousand patients with gastric cancer and CRC, comparing to individual application of chemotherapy, CIK/DC-CIK plus chemotherapy significantly increases overall survival and progression-free survival in drug-resistant patients, and swiftly improves most adverse events caused by chemotherapy ( 28 , 296 , 297 ). Similar results are also exhibited in CIK/DC-CIK therapy of pancreatic cancer and HCC, especially in advanced-stage patients ( 298 , 299 ). Interestingly, infusion of allogeneic CIKs has also demonstrated encouraging effects on hematological malignancies ( 300 ).…”
Section: Cellular Immunotherapy In Treatment Of Gastrointestinal Cancerssupporting
confidence: 80%
“…Through three meta-analysis studies of more than 8 thousand patients with gastric cancer and CRC, comparing to individual application of chemotherapy, CIK/DC-CIK plus chemotherapy significantly increases overall survival and progression-free survival in drug-resistant patients, and swiftly improves most adverse events caused by chemotherapy ( 28 , 296 , 297 ). Similar results are also exhibited in CIK/DC-CIK therapy of pancreatic cancer and HCC, especially in advanced-stage patients ( 298 , 299 ). Interestingly, infusion of allogeneic CIKs has also demonstrated encouraging effects on hematological malignancies ( 300 ).…”
Section: Cellular Immunotherapy In Treatment Of Gastrointestinal Cancerssupporting
confidence: 80%
“…Dendritic cell-based vaccines have been tested as therapeutic tool for HCC 45 . A recently reported meta-analysis aimed to investigate the efficacy of DCs alone or combined with conventional treatments illustrated that cellular immunotherapy improve prognosis by increasing overall survival and reducing recurrence in patients with advanced HCC 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Silencing of CXCL12 by transforming growth factor- β in mesenchymal stromal cells of the primary tumor site promoted the tumor metastasis by increasing the expression of CXCR7, a CXCL12 receptor [ 43 ]. A meta-analysis showed that immunotherapy with DCs significantly improved OS at 6 months, 1 year, 3 years, and 5 years of patients with hepatocellular carcinoma [ 44 ]. Coculture of DCs significantly inhibited liver cancer stem cell growth in vitro and in vivo [ 45 ].…”
Section: Discussionmentioning
confidence: 99%